Chigger mite (Eutrombicula alfreddugesi) ectoparasitism does not contribute to sex differences in growth rate in eastern fence lizards (Sceloporus undulatus) - Hailey Conrad; Nicholas B. Pollock; Henry John‐Alder (Ecology and Evolution, 2023)
Abstract Parasitism is nearly ubiquitous in animals and is frequently associated with fitness costs in host organisms, including reduced growth, foraging, and reproduction. In many species, males tend to be more heavily parasitized than females and thus may bear greater costs of parasitism. Sceloporus undulatus is a female‐larger, sexually size dimorphic lizard species that is heavily parasitized by chigger mites (Eutrombicula alfreddugesi). In particular, the intensity of mite parasitism is higher in male than in female juveniles during the period of time when sex differences in growth rate lead to the development of sexual size dimorphism (SSD). Sex‐biased differences in fitness costs of parasitism have been documented in other species. We investigated whether there are growth costs of mite ectoparasitism, at a time coinciding with sex differences in growth rate and the onset of SSD. If there are sex‐biased growth costs of parasitism, then this could suggest a contribution to the development of SSD in S. undulatus. We measured growth and mite loads in two cohorts of unmanipulated, field‐active yearlings by conducting descriptive mark‐recapture studies during the activity seasons of 2016 and 2019. Yearling males had consistently higher mid‐summer mite loads and consistently lower growth rates than females. However, we found that growth rate and body condition were independent of mite load in both sexes. Furthermore, growth rates and mite loads were higher in 2019 than in 2016. Our findings suggest that juveniles of S. undulatus are highly tolerant of chigger mites and that any costs imposed by mites may be at the expense of functions other than growth. We conclude that sex‐biased mite ectoparasitism does not contribute to sex differences in growth rate and, therefore, does not contribute to the development of SSD.